Guest

If 3 – x = -4, then x = . If 3 – x = -4, then x = . If 3 – x = -4, then x = .

 If 3 – x = -4, then x =                                 .
 If 3 – x = -4, then x =                                 .
 If 3 – x = -4, then x =                                 .

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5964 Points
one year ago
Dear Student

Consider the given equation, 3–x = -4
Transpose–x to RHS then it becomes x and–4 to LHS then it becomes 4,
3 + 4 =x
x= 7
Then, the value of x = 7

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free